Susceptibility Weighted Imaging: A Novel Method to Determine the Etiology of Aqueduct Stenosis - Chanabasappa Chavadi; Keerthiraj Bele; Anand Venugopal; Santosh Rai (Indian Journal of Neurosurgery)
Abstract The stenosis of aqueduct of Sylvius (AS) is a very common cause of obstruction to cerebrospinal fluid. Multiple etiologies are proposed for this condition. Because treatment is specific for correctable disorder, assessment of etiology gains importance. A case of pediatric hydrocephalus was diagnosed with stenosis of AS on magnetic resonance imaging (MRI). Susceptibility-weighted imaging (SWI) demonstrated blooming in the distal aqueduct and lateral ventricle, which was not seen on routine MRI sequences. The findings suggest that old hemorrhage is a cause of chemical arachnoiditis and adhesions causing aqueduct stenosis and hydrocephalus. To our knowledge literature is very scarce, wherein SWI is being used to confirm blood products as a cause of aqueduct stenosis; hence SWI should be routine protocol in imaging of pediatric hydrocephalus. Etiology, clinical presentation, role of imaging, and, in particular, SWI in evaluation of aqueductal stenosis is discussed.